Board game studies journal online (Associac̨ão Ludus, 2014)
Peer-reviewed international academic journal for historical and systematic research on board games. Its object is to provide a forum for board games research from all academic disciplines in order to further our understanding of the nature, development, and distribution of board games within an interdisciplinary context.